Brand Performance Analysis in the Insurance Industry (Explaining the Role of Cognitive and Affective Attitudes Using the S-O-R Framework and Brand Community) - Sedighi, Nooshin Sadat; Fattahi, Majid (Digital Transformation and Administration Innovation, 2025)
This study evaluates brand performance on social media by adopting the Stimulus-Organism-Response (S-O-R) framework to understand brand perception in the insurance industry. Employing an applied research approach, data were collected through a survey, and the analysis was conducted using structural equation modeling based on partial least squares (PLS-SEM). The statistical population consisted of Pasargad Insurance customers in Iran, from which a sample of 298 participants was selected using convenience sampling. The results indicated that brand community interaction significantly influences both cognitive and affective attitudes. Moreover, relationship investment in the community has a positive impact on brand community commitment and affective attitude but does not predict cognitive attitude. Additionally, both cognitive and affective attitudes influence brand loyalty and brand recommendation. The findings underscore the significance of all mediating relationships, except for the relationship between relationship investment in the community and brand performance through cognitive attitude. This study can assist companies in the insurance sector in enhancing their brand performance by engaging customers through managing appropriate stimuli.